Oxygen needs to be met in chad: Resilience, lessons learned, challenges and perspectives - Maombi, Edison; Ndihokubwayo, Jean-Bosco (Archives of Community Medicine and Public Health, 2023)
Lack of medical oxygen has contributed to a large number of avoidable fatalities globally, which have escalated as a result of the COVID-19 pandemic. At the start of the pandemic, one of the major challenges that almost all countries faced was access to oxygen to treat their patients, who were often doomed to certain death in the absence of this product. Chad had a total of two oxygen production plants, all installed in Ndjamena, with low production capacity to meet high demand. Oxygen concentrators, which are an appropriate and attractive means of administering oxygen in healthcare facilities where there is a shortage of cylinders or a distribution network, were also not sufficient, and most of them were out of use due to the lack of proper preventive maintenance. To overcome this situation, Chad is improving its capacity for medical oxygen through the installation of new Oxygen plants, maintenance and repair of broken Oxygen concentrators as well as the training of maintenance technicians. This paper shares the experience of Chad in its efforts to improve the availability of oxygen for the management of respiratory diseases, as well as the benefits and challenges to consider when planning for increased access to medical oxygen in similar settings.